2001
DOI: 10.1021/la000609d
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ultrathin Poly(ethylene glycol) Monolayers on Silicon Substrates

Abstract: Low molecular weight poly(ethylene glycol) silanes (PEG silanes) have been grafted onto the surface of silicon wafers in a one-step procedure yielding ultrathin and stable PEG monolayers. Structural investigation by means of X-ray reflectivity provided data on the thickness of the PEG monolayers. The layer thickness varied between 10 and 17 Å depending on the PEG silane concentration applied. These results have been confirmed by X-ray photoelectron spectroscopy measurements. Atomic force microscopy data indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
240
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(271 citation statements)
references
References 27 publications
28
240
0
3
Order By: Relevance
“…43 No. 1) were cleaned using 1:1 HCl/methanol followed by a concentrated H 2 SO 4 soak for 2 h. The coverslips were then coated with a PEG-terminated silane following a modified protocol from Papra et al 46 Dry toluene was prepared by distillation over metallic sodium to remove any water or other contaminants. The alkylsilane (2-[methoxypol(ethyleneoxy)proply]trimethoxysilane, Gelest, Tullytown, PA) was added to the toluene to a final concentration of 0.1% by volume in an MBraun glovebox (MBraun, Stratham, NH).…”
Section: ■ Discussionmentioning
confidence: 99%
“…43 No. 1) were cleaned using 1:1 HCl/methanol followed by a concentrated H 2 SO 4 soak for 2 h. The coverslips were then coated with a PEG-terminated silane following a modified protocol from Papra et al 46 Dry toluene was prepared by distillation over metallic sodium to remove any water or other contaminants. The alkylsilane (2-[methoxypol(ethyleneoxy)proply]trimethoxysilane, Gelest, Tullytown, PA) was added to the toluene to a final concentration of 0.1% by volume in an MBraun glovebox (MBraun, Stratham, NH).…”
Section: ■ Discussionmentioning
confidence: 99%
“…al. 1 for functionalizing the chips with PEG silane. PEG silane and concentrated HCl were mixed in toluene in a freshly cleaned glass beaker with 100 µL PEG and 40 µL HCl present in 50 mL of toluene.…”
Section: Functionalization Of Silicon With Peg Groupsmentioning
confidence: 99%
“…11 Work has shown that it is possible to pattern the aminated alkylsilane DETA using deep-ultraviolet ͑DUV͒ photolithography. [12][13][14][15][16] Using DUV, SAMs were exposed to intense ultraviolet light from an ArF excimer laser ͑emission wavelength 193 nm͒. Upon exposure the SAM underwent a photochemical reaction that cleaved the carbon-nitrogen bonds within the molecule, thereby removing the cytophilic surface coating.…”
Section: Introductionmentioning
confidence: 99%